Mica Can Alleviate TNBS-Induced Colitis in Mice by Reducing Angiotensin II and IL-17A and Increasing Angiotensin-Converting Enzyme 2, Angiotensin 1-7, and IL-10 - Mengdie Shen; Bibi Zhang; Mengyao Wang; Li’na Meng; Bin Lv (Mediators of Inflammation)
Aim. To explore the treatment effect of mica on 2,4,6-trinitrobenzenesulfonic acid solution- (TNBS-) induced colitis in mice. Materials and Methods. Thirty male BALB/C mice were randomly divided into the control group, the TNBS group, and the mica group. Control mice were treated with saline solution. Experimental colitis was induced by TNBS (250 mg/kg/d) in the TNBS group and the mica group. After modeling, the mica group was treated with mica (180 mg/kg/d) for 3 days, while the TNBS group continued the treatment with TNBS. All solutions were injected intrarectally. During treatment, body weight and mice activity were monitored daily. After treatment, the colon tissues of mice were collected; angiotensin II (Ang II), angiotensin-converting enzyme 2 (ACE2), angiotensin 1-7 (Ang (1-7)), IL-17A, and IL-10 expression was analyzed by ELISA and immunohistochemistry. Results. Food intake, activity, and body weight gradually decreased in the TNBS group compared to the control group and the mica group (all P<0.05). Also, black stool adhesion in the anus and thin and bloody stool were observed in the TNBS group, but not in the other two groups. Moreover, the expression of Ang II, ACE2, Ang (1-7), IL-17A, and IL-10 in the TNBS group increased compared to that in the control group. Compared to the TNBS group, ACE2, Ang (1-7), and IL-10 in the mica group increased, while Ang II and IL-17A decreased (all P<0.05). Conclusion. Mica can alleviate TNBS-induced colitis in mice by regulating the inflammation process; it reduces Ang II and IL-17A and increases ACE2, IL-10, and Ang (1-7).